Capsaicinoid Contents in Peppers and Pepper-Related Spicy Foods. Issue 3 (3rd March 2016) - Barbero, Gerardo Fernández; Liazid, Ali; Azaroual, Latifa; Palma, Miguel; Barroso, Carmelo García
Abstract : The quantification of the major capsaicinoids, namely nordihydrocapsaicin, capsaicin, dihydrocapsaicin, homocapsaicin, and homodihydrocapsaicin, present in spicy foods made from peppers has been performed. The capsaicin content is directly related to the pungency properties of foods that contain hot peppers. The samples studied included 10 different dried hot peppers, 19 hot sauces, 4 kinds of paprika, and 4 different ketchups. The range of concentrations of capsaicinoids found were as follows: dried hot peppers (554.1–1705.9 mol kg −1 ), paprikas (582.0–665.0 mol kg −1 ), spicy ketchups (4.0–12.4 mol kg −1 ), and hot sauces (4.6–843.8 mol kg −1 ). Variability in the capsaicinoid content was found, with capsaicin and dihydrocapsaicin present at the highest levels. The capsaicin content was generally higher than the dihydrocapsaicin content.